FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MAHASISWA MEMILIH FAKULTAS EKONOMI UNIVERSITAS ISLAM SUMATERA UTARA AL MUNAWAROH MEDAN - Suryani, Wan (Jurnal Ekonomi Modernisasi, 2013)
In this globalization era competition among universities to attract students getting tougher. It is therefore universities should further strenghten its marketing strategy, so that they can attract new students to decide to study in the Faculty of Economics, Islamic University of North Sumatra, Medan. This study aims to determine what factors are influencing students in choosing education at Faculty of Economics, Islamic University of Al Monawaroh Medan North Sumatra. The number of samples used in this study were 83 people who are students at the Faculty of Economics, Islamic University of Al Munawaroh Medan North Sumatra. Sampling performed by the method of proportionate random sampling. Data were collected using questionnaires. Variables Measurement with Likert scale in 5 (five) scale. Prior to data collection, questionnaire were testedÂ  by validity and reliability test using 30 (thirty) respondents. The validity test using the Pearson correlation thatÂ  correlate each item with total score of items and the reliability test using Cronbach Alpha. The result shows that factors must consider by the student when decided the Economy Faculty of UISU Al Munawaroh Medan are process, motivation, physical evidence, reference, cost, and location